The Phenomenon of Burnout of Primary School Teachers - Katarzyna Miłek; Magdalena Figaj (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Occupational burnout is a significant threat to the teaching profession, affecting both the quality of education and the mental health of educators. This study explores the phenomenon of burnout among primary school teachers, focusing on the dimensions of emotional exhaustion, depersonalization, and personal accomplishment. Using a quantitative approach, the research examined 31 teachers at Arkady Fiedler Primary School No. 5 in Gniezno. Results indicate that while 66.6% of respondents experience some level of emotional exhaustion, there is a strong correlation between professional experience and burnout severity. Teachers with over 30 years of service and those holding "certified teacher" status are most at risk. The study concludes that enhancing teachers' sense of self-efficacy and providing stress-management training are essential for organizational health.